Effects of Desert Land Cultivation on Soil Aggregate Stability and Carbon Fixation - Chen Xue; Liu Jiaqing; Li Min; Sun Jie; He Xuemin (Shuitu baochi tongbao)
[Objective] The response of soil aggregate stability and organic carbon before and after land reclamation using different land use types were analyzed in order to provide a scientific theoretical basis for wasteland reclamation, vegetation restoration, and agricultural production in the Ebinur Lake Wetland Reserve. [Methods] Five different land use types in the Ebinur Lake basin of Xinjiang were evaluated in this study: uncultivated natural forest land (CK), cultivated artificially planted lycium land, vitis land, cotton land, and alfalfa land. These land use types were selected to determine the response of soil structure and organic carbon content after land cultivation in a desert ecosystem. [Results] Land cultivation had significant effects on soil aggregate stability and carbon fixation in a desert area. After land cultivation, the content of macro aggregates (>0.25 mm) and the stability of aggregates of cultivated lands were significantly greater than those of CK. Cotton land had the highest content of force-stabilized macro aggregates (>87%). Lycium land had the highest content of water-stabilized macro aggregates (>79.7%). Different artificial tillage practices increased the content of macro aggregates. The particle size organic carbon contents in the aggregates of cultivated lands in the 0—30 cm soil layer were 5.91—15.46, 5.50—10.70, 8.12—16.11, and 6.90—13.67 g/kg, respectively. These values were significantly greater than the contents observed for CK (3.91—8.73 g/kg), mainly distributed in the 0.25—0.5 mm particle size. The organic carbon contents of soil aggregates increased significantly under all artificial land use practices, and the lycium land organic carbon content increased most significantly. [Conclusion] The cultivation practice of planting lycium barbarum after land cultivation was more conducive to increasing soil aggregate stability and improving organic carbon fixation than the other cultivation practices. Land cultivation can significantly increase soil carbon sequestration capacity and improve soil structure.